Delavski oder in amaterski učinek "proletarske igre" - Milohnić, Aldo (Amfiteater (Ljubljana), 2020)
In the historiography of Slovenian theatre, a commonly acknowledged thesis claims that socalled drama societies ( dramatična društva ) were the most important factor in the gradual transition from dilettantism to the professionalisation of Slovenian theatre. In the history of Slovenian theatre, a parallel stream existed - workers' stages, which were established in many of Slovenian cities, especially after World War I. These amateur theatres were driven primarily by the idea of social emancipation since the establishing of professional and national theatres was not their priority. Some of them, in particular, the Workers' Stage (Delavski oder) in Ljubljana, were staging quality performances. The thesis of this article is that the quality of the Workers' Stage was made possible by the distinctive way of performing that Bratko Kreft and Ferdo Delak developed when they were running it and also because the Workers' Stage did not succumb to the temptation of entering the nonproductive (and inevitably already lost) competition with Slovenian professional theatres. Additionally, Brecht's idea about "the simplicity of acting" that ought to be "the alpha and the omega of proletarian acting" can help us explain the success of Workers' Stage. In his opinion, the actors who practise "proletarian acting" are amateurs; however, they are by no means dilettantes. The article presents findings on the repertory and performing arts' practices of the Workers' Stage in Ljubljana using Brecht's perspective of this conceptual and methodological differentiation; by analogy with his "estrangement effect" ( Verfremdungseffekt ), we can call it the amateur effect of "proletarian acting".
Keywords: amatersko gledališče; amateur theatre; Bertolt Brecht; Branko Kreft; Delavski oder; delavsko gledališče; Ferdo Delak; proletarian acting; proletarska igra; Workers' Stage (Delavski oder); workers' theatre